2021
DOI: 10.2147/amep.s302728
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Educational Video on Blood Pressure Measurement for Pharmacy Students

Abstract: Introduction High blood pressure is an important worldwide health issue. Pharmacists can perform multifaceted tasks in hypertension management such as measuring blood pressure. In a time where the use of educational videos in health professions education has increased, an educational video might be an option for teaching blood pressure measurement skills to pharmacy students. This project aimed to develop an educational video tailored to pharmacy students on oscillometric blood pressure measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Smart phones are increasingly used in community health programmes [5,[12][13][14][15][16][17], but the use of video job-aids that can be displayed on smart phones or android devices has not been widely exploited. We investigated the use of video job-aids to support the delivery of seasonal malaria chemoprevention (SMC), and showed that the approach has many advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Smart phones are increasingly used in community health programmes [5,[12][13][14][15][16][17], but the use of video job-aids that can be displayed on smart phones or android devices has not been widely exploited. We investigated the use of video job-aids to support the delivery of seasonal malaria chemoprevention (SMC), and showed that the approach has many advantages.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted at a university primary care clinic from July 2022 to August 2023. It was conducted in three phases based on established literature 7 : pre-production phase (Phase 1), production phase (Phase 2) and post-production phase (Phase 3).…”
Section: Methodsmentioning
confidence: 99%
“… 6 Video-based interventions (VBIs) are valuable educational tools for patients that have been shown to enhance patients’ self-care practices. 7 VBIs have also been found to be more effective than printed pamphlets for both short-term behavioural change and longterm retention. 8 Other advantages of VBIs include cost-effectiveness, standardisation of teaching 9 and the ability for patients to view the material multiple times at their convenience.…”
Section: Introductionmentioning
confidence: 99%
“…In both study groups, a self-made self-instruction video, customized for pharmacy students, with a total length of 11 min 33 s was provided to the participants. It was meant to give pharmacy students a guide on how to measure the patient’s blood pressure accurately with an oscillometric upper arm device in a community pharmacy setting using a role-play format along with descriptive slides as a self-learning tool [ 50 ]. The video was provided on the university’s video platform and was accessible on-demand via the students’ identification data.…”
Section: Methodsmentioning
confidence: 99%